The Authentication of Hadith - Israr Ahmad Khan (International Institute of Islamic Thought, 2007)
Muslim scholars deserve appreciation for their invaluable contribution toward preserving the hadith literature’s authenticity. However, much more needs to be done to further strengthen its authenticity. Such great hadith authorities as Malik ibn Anas (d. 179 AH), Ahmad ibn Hanbal (d. 241 AH), al-Darimi (d. 255 AH), al-Bukhari (d. 256 AH), Muslim (d. 261 AH), Ibn Majah (d. 273 AH), Abu Da’ud (d. 275 AH), al-Tirmidhi (d. 279 AH), al-Nasa’I (d. 303 AH), al-Darqutni (d. 385 AH), and al-Bayhaqi (d. 457 AH) did their best to identify original, authentic, and valid versions of the hadiths, mainly through verifying the chain of narrators (sanad). However, they did not check the text (matn) with the same zeal. This remains the case today, even to the extent that scrutinizing the text scrutiny is considered forbidden. While further verification of hadiths is still needed, this “closed door” toward verifying the text’s validity must be opened. The present article represents an attempt to redefine the criteria for checking the texts and then applying these criteria to certain selected hadiths recorded by al-Bukhari and Muslim.